A lithium phosphide-based composite material and its preparation method and application

By combining lithium phosphide with graphene fluorinated, the problems of low conductivity and water sensitivity in lithium phosphide materials in lithium ion batteries are solved, and higher conductivity and chemical stability are achieved, improving the overall performance of lithium ion batteries.

CN116365062BActive Publication Date: 2025-02-28HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310142012.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-02-28
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

When existing lithium phosphide materials are used as lithium supplement material in lithium-ion batteries, their conductivity is low and water-sensitive, resulting in stability and performance problems in their applications.

Method used

By compounding lithium phosphide with graphene fluorinated, the high electron conductivity and two-dimensional nanostructure of graphene fluorinated graphene are used to improve the conductivity of lithium phosphide, and the chemical stability is improved by dispersing lithium phosphide between the graphene fluorinated graphene layers.

Benefits of technology

It significantly improves the electronic conductivity and chemical stability of lithium phosphide-based composite materials, and improves the circulation performance and stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium phosphide-based composite material and a preparation method and application thereof, belonging to the technical field of secondary battery materials. The lithium phosphide-based composite material provided by the present invention comprises fluorinated graphene, and lithium phosphide dispersed on the surface and between layers of the fluorinated graphene. The lithium phosphide-based composite material proposed by the present invention can effectively improve the conductivity of lithium phosphide when used as a lithium supplement material and reduce its sensitivity to water. The present invention also provides a preparation method and application of the above-mentioned lithium phosphide-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a lithium phosphide-based composite material and a preparation method and application thereof. Background Art

[0002] The energy density of commercial lithium-ion batteries is approaching its theoretical limit. In order to further improve the energy density of lithium-ion batteries, the development of new electrode materials with high specific capacity is extremely important. When the negative electrode contains high-capacity silicon-based materials or tin-based materials such as partial silicon, silicon carbon, silicon oxide, etc., the active lithium in the positive electrode is further consumed to meet the growth of the SEI film (solid electrolyte interphase) on the surface of the negative electrode and some irreversible alloying reactions, which ultimately leads to the loss of active lithium in the whole battery and a significant decrease in the first (first few weeks) coulombic efficiency.

[0003] In order to overcome the above shortcomings, researchers are working hard to develop lithium supplement materials to replenish the active lithium consumed in the process of SEI film formation. Lithium phosphide (Li3P) is considered to be an excellent lithium supplement material due to its extremely high specific capacity (1550mAh / g). However, its lithium supplement application is still limited by several aspects. First, it is currently difficult to prepare lithium phosphide with high purity. Second, lithium phosphide is an electronic insulator, and its room temperature lithium ion conductivity is also very low (<10 -8 S cm -1 ) is not conducive to the rapid transmission of lithium ions. Thirdly, lithium phosphide is extremely unstable in the air and easily reacts with water to produce lithium hydroxide and highly toxic phosphine, making it extremely difficult to further optimize and apply lithium phosphide materials.

[0004] Therefore, it is necessary to find a method to improve the performance of lithium phosphide materials and promote their application in the field of lithium supplementation. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium phosphide-based composite material, which can effectively improve the conductivity of lithium phosphide when used as a lithium supplement material and reduce its sensitivity to water.

[0006] The present invention also provides a method for preparing the lithium supplement material.

[0007] The present invention also provides application of the lithium supplement material.

[0008] According to an embodiment of the first aspect of the present invention, a lithium phosphide-based composite material is provided. The lithium phosphide-based composite material includes fluorinated graphene and lithium phosphide dispersed on the surface and between layers of the fluorinated graphene.

[0009] The lithium phosphide-based composite material according to the embodiment of the present invention has at least the following beneficial effects:

[0010] (1) The lithium phosphide-based composite material provided by the present invention includes fluorinated graphene, and thus has the electronic conductivity of fluorinated graphene. Therefore, when the lithium phosphide-based composite material is used as a lithium supplement for a secondary battery, it has a higher electronic conductivity.

[0011] (2) In the lithium phosphide-based composite material provided by the present invention, lithium phosphide is dispersed between the layers of fluorinated graphene, so that the fluorinated graphene isolates the lithium phosphide from the external environment, thereby improving the chemical stability of lithium phosphide and solving the air sensitivity of lithium phosphide to a certain extent. When it is used as a lithium supplement for lithium batteries, it can significantly improve the cycle performance and stability of lithium batteries.

[0012] (3) The rich CF bonds and two-dimensional nanostructure of fluorinated graphene are beneficial to Li + In the storage and diffusion of the charge and discharge process, the lithium phosphide-based composite material provided by the present invention significantly improves the Li + The electrical conductivity is improved, and finally the comprehensive electrochemical performance of lithium phosphide-based composite materials when used as lithium supplements.

[0013] (4) The mutual bonding structure of fluorinated graphene and lithium phosphide is not a rigid structure. The interlayers of fluorinated graphene cannot be completely filled with lithium phosphide. Therefore, when it is used as a lithium supplement for lithium-ion batteries, the lithium phosphide-based composite material can also accommodate part of the volume change during the charging and discharging process of the lithium-ion battery, thereby improving the comprehensive electrochemical performance of the resulting lithium-ion battery.

[0014] According to some embodiments of the present invention, the mass ratio of the fluorinated graphene to lithium phosphide is 1:0.1 to 9. For example, it may be 1:1, 6:1 or 9:1.

[0015] According to some embodiments of the present invention, the thickness of the fluorinated graphene is 50-150 nm.

[0016] According to some embodiments of the present invention, the ionic conductivity of the lithium phosphide-based composite material is ≥ 0.57×10 -2 S cm -1 .

[0017] According to some embodiments of the present invention, the electronic conductivity of the lithium phosphide-based composite material is ≥1.09×10 -2 S cm -1 .

[0018] According to an embodiment of the second aspect of the present invention, a method for preparing the above-mentioned lithium phosphide-based composite material is proposed, which specifically includes mechanically grinding the lithium phosphide and fluorinated graphene.

[0019] Since the preparation method adopts all the technical solutions of the lithium phosphide-based composite material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0020] In addition, the present invention realizes the compounding of the lithium phosphide and the fluorinated graphene through simple mechanical grinding, and the preparation method is simple and easy to realize.

[0021] According to some embodiments of the present invention, the method for preparing lithium phosphide includes mixing an organic solution of metallic lithium and red phosphorus for reaction.

[0022] According to some embodiments of the present invention, the preparation process of lithium phosphide is carried out in an environment isolated from air, for example, it can be carried out in a glove box filled with nitrogen or argon.

[0023] According to some embodiments of the present invention, the method for preparing the organic solution includes adding the metallic lithium into an organic solvent and stirring;

[0024] The stirring of the organic solution is configured to last for 0.5 to 2 hours.

[0025] According to some embodiments of the present invention, in the organic solution, the mass percentage of the metallic lithium is 10-60%, for example, about 10%, 30% or 40%.

[0026] According to some embodiments of the present invention, the organic solvent includes at least one of a mixture of benzene and tetrahydrofuran, a mixture of naphthalene and tetrahydrofuran, a mixture of biphenyl and tetrahydrofuran, a mixture of terphenyl and tetrahydrofuran, a liquid ammonia solution (CAS: 7664-41-7), a methylamine solution (CAS: 74-89-5), a dimethylamine solution (CAS: 124-40-3), an ethylamine solution (CAS: 75-04-7) and an ethylenediamine solution (CAS: 107-15-3).

[0027] According to some embodiments of the present invention, when the organic solvent includes tetrahydrofuran, the mass ratio of the remaining organic solvent to tetrahydrofuran is 0.5 to 5: 1. For example, in a mixture of benzene and tetrahydrofuran, the mass ratio of benzene to tetrahydrofuran is 0.5 to 5: 1. For example, it can be about 3:1.

[0028] According to some embodiments of the present invention, the red phosphorus includes pretreatment before use.

[0029] The pretreatment includes removing oxides on the surface of the red phosphorus using sodium hydroxide. Specifically, the red phosphorus and sodium hydroxide aqueous solution are mixed at a temperature of 60 to 100° C., for example, about 80° C.

[0030] According to some embodiments of the present invention, the mass ratio of the metallic lithium to the red phosphorus is 1:0.1-9, for example, specifically about 9:1 or 3:1.

[0031] According to some embodiments of the present invention, the mixing reaction includes stirring and standing in sequence, wherein the stirring is to increase the mass transfer rate and promote the full progress of the mixing reaction, and the standing is to promote the precipitation of the generated lithium phosphide.

[0032] According to some embodiments of the present invention, the stirring time in the mixing reaction is 1 to 3 hours, for example, about 2 hours.

[0033] According to some embodiments of the present invention, the duration of the standing time in the mixing reaction is 12 to 24 hours, for example, specifically about 12 hours.

[0034] According to some embodiments of the present invention, the temperature of the mixing reaction is 40-100° C., for example, about 60° C.

[0035] According to some embodiments of the present invention, the method for preparing lithium phosphide further comprises performing solid-liquid separation after the mixing reaction, and drying the obtained solid product.

[0036] According to some embodiments of the present invention, a method for preparing lithium phosphide comprises the following steps:

[0037] S1a. Pretreating the red phosphorus with the sodium hydroxide;

[0038] Dissolving the metallic lithium in the organic solvent to form the organic solution;

[0039] S1b. The red phosphorus obtained in step S1a and the organic solution are mixed for reaction;

[0040] S1c. The system obtained in step S1b is subjected to solid-liquid separation, and the solid product obtained is dried to obtain the lithium phosphide;

[0041] The lithium phosphide is prepared in an environment isolated from air.

[0042] The lithium phosphide prepared by the above preparation method has high purity.

[0043] According to some embodiments of the present invention, the step of preparing fluorinated graphene includes subjecting a mixture of graphene oxide and hydrofluoric acid to a hydrothermal reaction.

[0044] According to some embodiments of the present invention, the method for preparing graphene oxide includes using graphite as a raw material and adopting Hummers preparation.

[0045] According to some embodiments of the present invention, in the hydrothermal reaction, the concentration of HF in the hydrofluoric acid is 10-25 mol / L, for example, about 15 mol / L.

[0046] According to some embodiments of the present invention, in the hydrothermal reaction, the solid content of the graphene oxide is 80%-99%.

[0047] According to some embodiments of the present invention, the temperature of the hydrothermal reaction is 120°C-180°C. For example, it may be about 150°C.

[0048] According to some embodiments of the present invention, the duration of the hydrothermal reaction is 6-24 hours, for example, about 12 hours or 16 hours.

[0049] According to some embodiments of the present invention, the preparation of fluorinated graphene further comprises performing solid-liquid separation after the hydrothermal reaction, and washing the obtained solid product with water until it is neutral.

[0050] According to some embodiments of the present invention, the mechanical grinding method includes ball milling;

[0051] The grinding beads of the ball mill are zirconia beads.

[0052] According to some embodiments of the present invention, during the ball milling process, the rotation speed of the ball mill is 200-1000 rpm; for example, specifically, it may be about 400 rpm.

[0053] According to some embodiments of the present invention, the ball milling time is 24 to 100 hours, for example, about 36 hours or 72 hours.

[0054] According to some embodiments of the present invention, during the ball milling process, the ball-to-material ratio is about 2:3.

[0055] The ball milling process is not temperature regulated, that is, is carried out at room temperature.

[0056] According to an embodiment of the third aspect of the present invention, there is provided a use of the lithium phosphide-based composite material in a lithium-replenishing material for a positive electrode of a lithium-ion battery.

[0057] Since the application adopts all the technical solutions of the lithium phosphide-based composite material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0058] In addition, in the lithium phosphide-based composite material, the lithium phosphide crystal has a capacity of 1547.61 mAh·g -1The decomposition potential is 1V, which is much lower than the cut-off voltage of the positive electrode. The delithiation of lithium phosphide is an irreversible process and only participates in the first charging process. Therefore, the lithium phosphide-based composite material can be used for positive electrode lithium replenishment, but not for negative electrode lithium replenishment, and has the effect of increasing the capacity of lithium-ion batteries.

[0059] According to some embodiments of the present invention, in the application, in the negative electrode matching the positive electrode of the lithium-ion battery, the negative electrode active material includes a silicon-based material.

[0060] According to an embodiment of the fourth aspect of the present invention, a lithium-ion secondary battery is provided. The lithium-ion secondary battery includes a positive electrode, and raw materials for preparing the positive electrode include a positive electrode active material and the lithium phosphide-based composite material.

[0061] Since the lithium-ion secondary battery adopts all the technical solutions of the lithium phosphide-based composite material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, that is, the lithium-ion secondary battery has the advantages of high initial coulombic efficiency, high capacity and good cycle performance.

[0062] According to some embodiments of the present invention, the mass percentage of the lithium phosphide-based composite material to the positive electrode active material is 0.2-1%, for example, specifically about 0.5%.

[0063] According to some embodiments of the present invention, the cathode active material comprises at least one of a polyanion cathode material and a layered cathode material;

[0064] The polyanion material includes at least one of lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate;

[0065] The layered positive electrode material includes lithium-rich material, lithium cobalt oxide material, lithium nickel oxide material, lithium manganese oxide material, lithium nickel manganese oxide material, lithium nickel cobalt oxide material, lithium manganese cobalt oxide material, and lithium nickel cobalt manganese oxide material, as well as at least one of the materials formed by coating, doping, and blending the above materials.

[0066] According to some embodiments of the present invention, the lithium-ion secondary battery further comprises a negative electrode matching the positive electrode;

[0067] The raw materials for preparing the negative electrode include negative electrode active materials;

[0068] The negative electrode active material includes at least one of a graphite-based material, a silicon-based material and a tin-based material;

[0069] The silicon-based material includes silicon-oxygen material.

[0070] When the negative electrode active material includes the silicon-based material, the performance of the lithium phosphide-based composite material as a positive electrode lithium supplement is more excellent.

[0071] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0072] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0073] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0075] Figure 1 This is a scanning electron microscope image of the lithium phosphide-based composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0076] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0077] Example 1

[0078] This embodiment prepares a lithium phosphide-based composite material, and the specific steps are as follows:

[0079] Preparation of Li3P in a glove box with Ar atmosphere:

[0080] The red phosphorus and the sodium hydroxide aqueous solution are mixed at 80° C. for pretreatment to remove surface oxides. In this step, the concentration of the sodium hydroxide aqueous solution and the mixing time are not limited as long as the oxides on the surface of the red phosphorus can be removed.

[0081] Metallic lithium is dissolved in an organic solvent and stirred for 0.5 hours to obtain an organic solution; the mass percentage of metallic lithium is 10%; the organic solvent used is a mixture of benzene and tetrahydrofuran in a mass ratio of 3:1.

[0082] The temperature was controlled at 60° C., the pretreated red phosphorus was added to the organic solution, stirred for 1 hour, allowed to stand for 12 hours, and then centrifuged. The obtained product was dried to obtain Li3P. The mass ratio of metallic lithium to red phosphorus was 1:9.

[0083] Preparation of fluorinated graphene (FG):

[0084] First, graphene oxide was prepared from graphite by Hummers, and then hydrofluoric acid (concentration of 15 mol / L) and graphene oxide dispersion were added into the reactor. Then, the mixture was hydrothermally reacted at 150°C (the solid content of graphene oxide in the reaction system was 80%) for 16 hours. After the reaction, the mixture was washed with deionized water until the pH was neutral.

[0085] Preparation of lithium phosphide-based composite materials (Li3P@FG): fluorinated graphene powder and Li3P were placed in a zirconia ball mill with a mass ratio of 1:9; Li3P@FG composite materials were obtained by mechanical ball milling; wherein the ball mill speed was 400 rpm, the grinding balls were zirconia balls, the ball-to-material ratio was 2:3, and the ball milling time was 72 h.

[0086] In this embodiment, there is no order between the steps of preparing fluorinated graphene and preparing Li3P, as long as both are performed before preparing the lithium phosphide-based composite material;

[0087] In the process of preparing Li3P, there is no order between the pretreatment of red phosphorus and the preparation of the organic solution.

[0088] The morphology test shows that the lithium phosphide-based composite material obtained in this example is a composite of granular material and thin film material, in which the granular material is filled in the interlayer of the thin film material. This proves that the lithium phosphide is located in the interlayer and surface of the fluorinated graphene, and the thickness of the fluorinated graphene is about 50nm. The specific test results are as follows Figure 1 shown.

[0089] The ionic conductivity of the lithium phosphide-based composite material obtained in this example is 0.57×10 -2 S cm -1 , electronic conductivity ≥1.09×10 -2 S cm -1 .

[0090] Example 2

[0091] This embodiment prepares a lithium phosphide-based composite material, which is different from Embodiment 1 in that:

[0092] (1) During the preparation of Li3P:

[0093] The mass percentage of metallic lithium in the organic solution is 30%;

[0094] The mass ratio of metallic lithium to red phosphorus is 3:1;

[0095] (2) During the preparation of lithium phosphide-based composite materials:

[0096] The mass ratio of fluorinated graphene powder to Li3P is 1:1.

[0097] Example 3

[0098] This embodiment prepares a lithium phosphide-based composite material, which is different from Embodiment 1 in that:

[0099] (1) During the preparation of Li3P:

[0100] Stir for 1 hour to obtain an organic solution, in which the mass percentage of metallic lithium is 40%;

[0101] During the reaction of the organic solution and red phosphorus, the mixture was stirred for 2 h and allowed to stand for 24 h;

[0102] The mass ratio of metallic lithium to red phosphorus is 9:1;

[0103] (2) During the preparation of lithium phosphide-based composite materials:

[0104] The mass ratio of fluorinated graphene powder to Li3P is 6:1.

[0105] Comparative Example 1

[0106] This comparative example prepares a lithium phosphide-based composite material, which is different from Example 1 in that:

[0107] The method only comprises the step of preparing Li3P, i.e. using Li3P as a lithium phosphide-based composite material;

[0108] In the step of preparing Li3P, the mass ratio of metallic lithium to red phosphorus is 3:1.

[0109] Comparative Example 2

[0110] This comparative example prepares a lithium phosphide-based composite material, which is different from Example 2 in that:

[0111] (1) During the preparation of Li3P:

[0112] The mass percentage of metallic lithium in the organic solution is 30%;

[0113] (2) The step of preparing fluorinated graphene is not included;

[0114] (3) In the step of preparing the lithium phosphide-based composite material, the FG in Example 1 is replaced with an equal amount of reduced graphene oxide.

[0115] The reduced graphene oxide of this comparative example is obtained by reducing the graphene oxide prepared by the Hummers method using a reducing agent (ascorbic acid), wherein the mass ratio of the reducing agent to the graphene oxide is 1:1.

[0116] Test Case

[0117] This test example uses the performance of the lithium phosphide-based composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 as positive electrode lithium supplement agents, specifically:

[0118] The negative electrode active material is a mixture of artificial graphite (Shanshan Technology Co., Ltd.) and silicon-oxygen material (silicon oxide, Yijin New Energy Technology Co., Ltd.) in a mass ratio of 93:7;

[0119] The positive electrode active material is LiCoO2, and the amount of the positive electrode lithium supplement is 0.5% of the mass of the positive electrode active material;

[0120] The diaphragm adopts JL 7μm oil-based diaphragm;

[0121] The bare cell is obtained by fully automatic winding; the bare cell is sealed with an aluminum-plastic film outer package of a certain size, and a certain amount of electrolyte is injected into the dried semi-encapsulated cell to complete the encapsulation. The battery injection coefficient is 1.7, and the N / P value is 1.08.

[0122] The above-mentioned battery is further subjected to processes such as standing, forming, shaping and capacity division to complete the preparation of the lithium-ion soft-pack battery.

[0123] The prepared lithium-ion soft-pack battery (numbered as a specific embodiment of the lithium phosphide-based composite material source) was cycled at a temperature of 25°C ± 3°C, at a charge and discharge rate of 0.2C / 0.5C, within a voltage range of 3.0-4.48V, and the coulombic efficiency of the first week, the discharge gram-specific capacity, and the ratio of the gram-specific capacity of 700 weeks to the gram-specific capacity of the first week (capacity retention rate of 700 weeks) were recorded. The specific test results are shown in Table 1.

[0124] Table 1 Performance of the lithium phosphide-based composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 as positive electrode lithium supplement agents

[0125]

[0126]

[0127] The results in Table 1 show that when the lithium phosphide-based composite material provided by the present invention is used as a positive electrode lithium supplement, the first-cycle coulombic efficiency and gram-specific capacity of the obtained lithium-ion battery can be effectively improved.

[0128] However, if the lithium phosphide-based composite material does not include fluorinated graphene (Comparative Example 1) or replaces fluorinated graphene with traditional reduced graphene oxide, the first-week coulombic efficiency and gram-specific capacity of the obtained lithium ion battery will be significantly reduced. This shows that the mutual cooperation between fluorinated graphene and lithium phosphide can significantly improve the lithium replenishment effect of lithium phosphide. And in the lithium ion batteries corresponding to Examples 1 to 3, better cycle performance than that of Comparative Examples 1 to 2 is obtained, which shows that the lithium phosphide-based composite material provided by the present invention has weaker air sensitivity, and the lithium phosphide-based composite material after playing the role of lithium replenishment can also improve the cycle performance of lithium ion batteries to a certain extent.

[0129] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises a positive electrode and a negative electrode, and the raw materials for preparing the positive electrode comprise a positive electrode active material and a lithium phosphide-based composite material; the positive electrode active material comprises lithium cobalt oxide; In the negative electrode, the negative electrode active material includes graphite-based materials and silicon-based materials; The lithium phosphide-based composite material comprises fluorinated graphene and lithium phosphide dispersed on the surface and between layers of the fluorinated graphene; The mass percentage of the lithium phosphide-based composite material to the positive electrode active material is 0.2-1%; The mass ratio of the fluorinated graphene to lithium phosphide is 1:0.1-9; The preparation step of the fluorinated graphene includes subjecting a mixture of graphene oxide and hydrofluoric acid to a hydrothermal reaction; wherein, in the hydrothermal reaction, the concentration of HF in the hydrofluoric acid is 10-25 mol / L; the solid content of the graphene oxide is 80%-99%; the temperature of the hydrothermal reaction is 120°C-180°C; and the duration is 6-24h.

2. The lithium ion secondary battery according to claim 1, characterized in that: The method for preparing the lithium phosphide-based composite material comprises mechanically grinding the lithium phosphide and fluorinated graphene.

3. The lithium ion secondary battery according to claim 1, characterized in that: The method for preparing lithium phosphide comprises mixing an organic solution of metallic lithium and red phosphorus for reaction.

4. The lithium ion secondary battery according to claim 3, characterized in that: In the organic solution, the mass percentage of the metallic lithium is 10-60%.

5. The lithium ion secondary battery according to claim 3, characterized in that: The mixing reaction includes stirring and standing in sequence.

6. The lithium ion secondary battery according to claim 5, characterized in that: The stirring time is 1 to 3 hours.

7. The lithium ion secondary battery according to claim 5, characterized in that: The standing time is 12 to 24 hours.

Citation Information

Patent Citations

  • Preparation method of fluorinated graphene coated manganese, cobalt and lithium positive electrode material

    CN104538620A

  • Composite positive electrode material for lithium carbon fluoride battery and preparation method for composite positive electrode material

    CN107316988A

  • Composite material, method for producing composite material, method for manufacturing electrode, positive electrode and lithium ion secondary battery

    JP2021096928A